Pragmatic Reference in Elvis Gbanabom Hallowell's The Dining Table - Jegede, Olusegun Oladele (Journal of Pragmatics Research, 2020)
This study examined the pragmatic references used in Elvis Gbanabom Hallowell's poem, The Dining Table. The study adopted content analysis as its method. This involved the description and interpretation of referents (words used to refer to people, things and events in a special and indirect way) used in the poem. The poem was critically perused and the referents were identified and analysed. The referents were then interpreted and related to the ideologies expressed in the poem. The findings revealed that the poet used referents to point accusing finger to the events of war and the troubles that come with it. This was evident with the deployment of  referents such as dinner, tonight, gun wounds, desert tongues, vegetable blood, pepper, scorpions, guests, oceans of bowls, vegetables, tongues, the table, an island, guerrillas, crocodiles, surf, Alphabeta, empty palms, switchblades, silence, voices, playground, children`s toys, roadblocks, cup of life, ticks, cracked lips, milk, moon, revolutionary, Nile, tributaries, night, lovers of fire, gun wounds, boots, walk. The study concluded that the use of referents in the poem helped to express the brutality and horror of war, suffering, agony, revolution, the dark side of child soldiers, violence and blood bath. Above all, pragmatic reference helped to set the gloomy mood and sad tone of the poem. Keywords: Pragmatic Reference, Referent, Pragmatics, Meaning